Species richness and geographic distribution of testate amoebae (Rhizopoda) in Brazilian freshwater environments - Fábio Amodêo Lansac-Tôha (Acta Scientiarum. Biological Sciences, 2007)
The present study aimed to analyze the species richness of testate amoebae, as well as to describe their geographic distribution and different habitat types in Brazilian freshwater environments. Until now, 346 infrageneric taxa have been recorded, belonging to 13 families and 40 genera. In the Center-West region, 267 taxa were recorded; 188 taxa in the Southeast; 129 taxa in the South, 53 taxa in the North; and 18 taxa in Northeast region. A total of 282 taxa were recorded in plankton; 80 taxa in aquatic macrophytes; 81 taxa in sediment; and 73 taxa in moss/sphagnum. The results regarding testate amoebae species richness are not yet conclusive, given that most research on these organisms was carried out in central, southeastern and southern Brazil. The higher number of taxa observed in plankton may be due to the fact that most studies on testate amoebae in Brazil had been carried out in the planktonic compartment, including reservoirs, floodplain lagoons, channels, tributaries and rivers. In addition, the majority of studies with sediment samples were conducted in estuaries or coastal lagoons, where salinity is a restricting factor for the occurrence of these organisms.